South Asian Atlantic Literature, 1970-2010 - Maxey, Ruth (Book collections on Project MUSE., 2012)
The first major interpretation of recent South Asian diasporic writing in specifically transatlantic terms. Ruth Maxey offers readings of canonical and less well-known South Asian American and British Asian texts and key cinematic works. She explores the formal and thematic tendencies of the works, relating them to gender politics, the marketplace, and issues of literary value and historical change. The book engages with established debates, while intervening in new ways in transatlantic studies, postcolonial literary studies and Asian American cultural studies. Key features. Organised around four key themes: home & nation, travel & return, racial mixing and food & eating Writers studied range from Jhumpa Lahiri, Bharati Mukherjee, Mohsin Hamid, Hanif Kureishi, Monica Ali and Nadeem Aslam Engages with critics including Susan Koshy, Sukhdev Sandhu, Rajini Srikanth and James Procter Sources include articles from mainstream British, American and Asian newspapers such as New Statesman, The Daily Telegraph, The Guardian, The New York Times, The Washington Post and The Hindu Films studied include Mischief Night, Mississippi Masala, A Love Supreme and Praying with Anger